2017
DOI: 10.1097/ccm.0000000000002448
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival in a Long-Term Rat Model of Sepsis Is Associated With Reduced Mitochondrial Calcium Uptake Despite Increased Energetic Demand

Abstract: Objective: To investigate the relationship between prognosis, changes in mitochondrial calcium uptake and bioenergetic status in the heart during sepsis. Design:In vivo and ex vivo controlled experimental studies.Setting: University research laboratory. Subjects: Male adult Wistar rats.Interventions: Sepsis was induced by intraperitoneal injection of fecal slurry. Shamoperated animals served as controls. Confocal microscopy was used to study functional and bioenergetic parameters in cardiomycoytes isolated aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 53 publications
1
14
1
Order By: Relevance
“…A prior study, using a different sepsis animal model, reported reduced mitochondrial calcium uptake in isolated non-permeabilized rat cardiomyocytes. They suggested that reduced calcium uptake may underlie lower responsiveness to adrenergic challenge in septic rats [54]. In our study, LGM2605 increased calcium uptake in permeabilized cardiomyocytes but did not improve β-AR responsiveness.…”
Section: Discussioncontrasting
confidence: 51%
“…A prior study, using a different sepsis animal model, reported reduced mitochondrial calcium uptake in isolated non-permeabilized rat cardiomyocytes. They suggested that reduced calcium uptake may underlie lower responsiveness to adrenergic challenge in septic rats [54]. In our study, LGM2605 increased calcium uptake in permeabilized cardiomyocytes but did not improve β-AR responsiveness.…”
Section: Discussioncontrasting
confidence: 51%
“…Sepsis has recently been defined as “a life-threatening organ dysfunction caused by a dysregulated host response to infection” [ 1 ]. This dysregulation is particularly evident in the cells, organelles and overall system involved in the delivery and consumption of oxygen, or more specifically, the erythrocytes [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ], mitochondria [ 9 , 10 , 11 , 12 ] and microcirculation [ 13 , 14 , 15 , 16 ]. In this review, we consider the effect of sepsis on the red blood cell (RBC).…”
Section: Introductionmentioning
confidence: 99%
“…3a). In addition, when LPS = 4 the new model showed that energy response was at lower level which correspond the mitochondrial dysfunction and a consequence of a progressive decrease in energy availability during the septic process proposed by Singer et al [64][65][66][67][68][69][70][71][72]. Finally, we considered the result is similar to the immunosuppression mechanism associated with septic shock.…”
Section: In Silico Simulation Of Septic Shockmentioning
confidence: 74%
“…After introducing these virtual treatments into the initial model (data not shown), the activation of A at 0.2 h interrupted the formation of the irreversible SI* response and hyper-activated E. The results obtained after treatment in the later states (30,72, and 120 h) showed that the activation of anti-inflammation could reduce the hyper-activation of P, activate E, and possibly balance the immune system. By contrast, the inhibition of A in the long term led to the hyper-activation of P and E decreased.…”
Section: Virtual Treatmentsmentioning
confidence: 94%